Evaluation of Ketofol (Ketamine Propofol combination) as total intravenous anaesthetic for burn dressing in adult patient - Samad, MA; Islam, MS; Ahmed, M; Maruf, AA (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13534 JAFMC Vol.8(1) 2012 pp.20-24